2002
DOI: 10.1152/ajpheart.00808.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac myocyte adenosine A2areceptor activation fails to alter cAMP or contractility: role of receptor localization

Abstract: Adenosine A2a receptors are found in coronary vascular tissue although, their presence in myocardium is subject to investigation. Although there have been numerous studies on adenosine A2a receptor agonist effects on contractility and cAMP levels in ventricular myocytes, these have yielded conflicting results. Negative pharmacological studies have even led to the conclusion that A2a receptors are not present in cardiac myocytes. The purpose of this study was to determine whether A2a receptors are expressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
38
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 39 publications
5
38
1
Order By: Relevance
“…It is thought that both of these receptors exert their protection via direct effects on the cardiac myocytes, although to date there remains no definitive evidence that A 3 receptors are expressed in adult ventricular myocytes. Although there is evidence that adenosine A 2a receptors are expressed in ventricular cardiomyocytes (10,20), the results of a very limited number of studies indicate that the administration of A 2a receptor agonists before ischemia does not induce cardioprotection (1, 13, 32, 33). The results of the present in vivo study confirm the inability of a selective A 2a receptor agonist (CGS-21680) to reduce infarct size when administered before ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thought that both of these receptors exert their protection via direct effects on the cardiac myocytes, although to date there remains no definitive evidence that A 3 receptors are expressed in adult ventricular myocytes. Although there is evidence that adenosine A 2a receptors are expressed in ventricular cardiomyocytes (10,20), the results of a very limited number of studies indicate that the administration of A 2a receptor agonists before ischemia does not induce cardioprotection (1, 13, 32, 33). The results of the present in vivo study confirm the inability of a selective A 2a receptor agonist (CGS-21680) to reduce infarct size when administered before ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports that A 2a receptor postconditioning can be induced in isolated perfused heart preparations (35, 36) suggest that direct myocardial effects may be involved. It has also been reported that rat, porcine, and human ventricular myocytes express A 2a receptors (10,20), raising the possibility that A 2a receptor activation may modulate the cardiomyocyte response to ischemia-reperfusion.Although the administration of A 2a agonists before ischemia does not reduce infarct size, there are an increasing number of reports of interactions between A 1 and A 2a receptors. Interactions between adenosine A 1 and A 2a receptors have been reported in rat striatum and hippocampus (6, 8, 16 -18, 23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, A 2A R activation could not lead to any change in I h . A second possibility that may be pertinent to our results is the absence of functional A 2A R or A 3 R proteins in cardiac myocytes [10,30] . These two lines of evidence completely rule out the involvement of A 2A R and A 3 R in the present study.…”
Section: Discussionmentioning
confidence: 90%
“…A2AAR can be found in the brain [17], ventricular myocytes [18], endothelial cells [19], carotid body [20], and immune cells [20,21], among other tissues. With such a wide distribution, A2AAR has been linked to several processes, including protection against ischemia-reperfusion injury [22], coronary vasodilatation [23], sleep regulation [24], control of inflammation [21], citing but a few biological events related to such receptor.…”
Section: Adenosine Receptors-a Brief Overviewmentioning
confidence: 99%